Solve the equation
- 1
- m - 7 = 5
3

Answers

Answer 1
Answer:

1/3m-7=5

One solution was found :

m = 36
Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

1/3*m-7-(5)=0

Step by step solution :

Step 1 :

1
Simplify —
3
Equation at the end of step 1 :

1
((— • m) - 7) - 5 = 0
3
Step 2 :

Rewriting the whole as an Equivalent Fraction :

2.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

7 7 • 3
7 = — = —————
1 3
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

Adding fractions that have a common denominator :

2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

m - (7 • 3) m - 21
——————————— = ——————
3 3
Equation at the end of step 2 :

(m - 21)
———————— - 5 = 0
3
Step 3 :

Rewriting the whole as an Equivalent Fraction :

3.1 Subtracting a whole from a fraction

Rewrite the whole as a fraction using 3 as the denominator :

5 5 • 3
5 = — = —————
1 3
Adding fractions that have a common denominator :

3.2 Adding up the two equivalent fractions

(m-21) - (5 • 3) m - 36
———————————————— = ——————
3 3
Equation at the end of step 3 :

m - 36
—————— = 0
3
Step 4 :

When a fraction equals zero :

4.1 When a fraction equals zero ...
Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.

Here's how:

m-36
———— • 3 = 0 • 3
3
Now, on the left hand side, the 3 cancels out the denominator, while, on the right hand side, zero times anything is still zero.

The equation now takes the shape :
m-36 = 0

Solving a Single Variable Equation :

4.2 Solve : m-36 = 0

Add 36 to both sides of the equation :
m = 36

One solution was found :

m = 36

I happen this help

Related Questions

The mean life of a television set is 119 months with a standard deviation of 13 months. If a sample of 67 televisions is randomly selected, what is the probability that the sample mean would differ from the true mean by less than 2 months? Round your answer to four decimal places.
Solve the equation: b/5 + 15 =45is answer 150
Graph the following function and then find the specified limits. When necessary, state that the limit does not exist.f(x)equals=left brace Start 3 By 2 Matrix 1st Row 1st Column x minus 3 2nd Column if x less than 5 2nd Row 1st Column 2 2nd Column if 5 less than or equals x less than or equals 6 3rd Row 1st Column x plus 4 2nd Column if x greater than 6 EndMatrixx−3 if x<52 if 5≤x≤6x+4 if x>6;findModifyingBelow lim With x right arrow 5limx→5 f(x)andModifyingBelow lim With x right arrow 6limx→6 f(x)
Find the slope and the y-intercept of the line.y=2x-7
You buy 1.95 pounds of oranges and 1.65 pounds of apples. Oranges and apples sell for the same price per pound. The total​ cost, after using a 75¢​-off ​coupon, is ​$2.49. If c represents the cost of the fruit in dollars per​ pound, what equation could you use to find the value of​ c?

What property allows us to determine the congruency of the two triangles in the diagram?A. SSS
B. ASA
C. HL
D. SAS

Answers

A. SSS

That is because the diagram only shows that the sides are congruent and does not show anything else. (Like angles or anything)

The correct answer is A.SSS.

P.S. I am only answering this question so you could give the brainliest to the person who answered first :)

The following is known about three numbers: If the second number is subtracted from the sum of the first number and 3 times the third number, the result is 2. The third number plus 3 times the first number is -1. The first number plus 3 times the second number plus the third number is -16. Find the sum of the three numbers.

Answers

Answer:

-6

Step-by-step explanation:

Let the first, second and third number be x, y and z respectively.

We are told that the second number is subtracted from the sum of the first number and 3 times the third number, the result is 2.

Thus;

(x + 3z) - y = 2 - - - (eq 1)

The third number plus 3 times the first number is -1.

Thus;

z + 3x = -1 - - - (eq 2)

The first number plus 3 times the second number plus the third number is -16.

Thus;

x + 3y + z = -16 - - - (eq 3)

From eq 2, we can rearrange to get;

z = -1 - 3x

Putting -1 - 3x for z in eq(1) and (eq 3),we have;

(x + 3(-1 - 3x)) - y = 2

x -3 - 9x - y = 2

-8x - y = 2 + 3

-8x - y = 5

y = -5 - 8x

Putting y = -5 - 8x and z = -1 - 3x into eq(3), we have;

x + 3(-5 - 8x) + (-1 - 3x) = -16

x - 15 - 24x - 1 - 3x = -16

-26x - 16 = -16

-26x = 16 + 16

x = 0

Since y = -5 - 8x, then y = -5 - 8(0)

y = - 5

Also, since z = -1 - 3x, then;

z = -1 - 3(0)

z = -1

The sum of the three numbers are;

x + y + z = 0 + (-5) + (-1) = -6

50 pointsssssss
HELPPPPP NOWWW

Answers

Answer:

The third or fifth answer but mostly third the glaboal depression known as great depression was mostly known for people getting mad because their work checks decreased this caused a lot of people to not work and quit their jobs now that you think of it mabye you can choose a or c please choose both or one these are most recommended........... so i did some research and the answer is #1

the second one is becasue great depression had nothing to do with europe

the third was wrong becasue when the market crash happended peploe did refuse but that not how it affected them

the fourth one during the great depriosn no one was even able to trade except the goverment and its ovidious

the fifth their was no reason for their money to be declined

Officialanswer:Thefirstanswer/A

Step-by-step explanation:

please give brainliest

hi i hope this helps and you shoukd use the brainpop great depression video to help more and lastly, i love you as a friend becasue i have nothing to do so yeah bye :p

Is the Mean Value Theorem applicable to the function f(x) = |x - 1| on the interval [0, 2]?Why or why not?

Answers

The only point that derivative of the function f(x) = |x - 1| is not continuous is at x = 0. You need to check whether the slope for the interval (0,2) is continuous to see if you can apply MVT. The interval (0,2) does not include end points, so 0 is not in this interval. The function is continuous over the interval, so MVT can be applied.

Given the equation: 3x − 4y = 8,a) write an equation of a line parallel that passes through the point (-16, 4).

b) write an equation of a line perpendicular that passes through the point (9, -7).

Answers

Answer:

use slope intercept formula

y=Mx +b

Step-by-step explanation:

3X-4Y=8

3X-8 = 4Y

y = 3/4x-2

our new equation just needs to have the same slope  M= 3/4

y-y1=M(x-x1)

y-4=3/4(x-(-16))

y=3/4x+12+4

y=3/4x+16  answer a

for a perpendicular line.. just take the inverse of the slope... and change the sign.  so now our slope is - 4/3

plug in our new point (9,-7)

y-(-7) = -4/3(x-9)

y+7=-4/3x+12

y= -4/3x +5 answer b

Proportional relationships

Answers

Answer:

relationships between two variables where their ratios are equivalent. Another way to think about them is that, in a proportional relationship, one variable is always a constant value times the other.

Step-by-step explanation: